Ten years of the journal Radiology and oncology - Musek, Matjaž (Radiology and oncology (Ljubljana), 2003)
Background. Bibliometrics and its methods are a useful set of tools for analysing a scientific journal's relative position in the field. By measuring different quantitative data and comparing them with other journals in the field, certain decisions can be made as to the future of the journal. Objectives and methods. We thought as appropriate to take last ten years of Radiology and Oncology (1992-2001) and put that content to double scrutiny: first, by applying various guantitative measurements to the journal's content to get a more objective picture of the whole and of its development in the past ten years; then by additionally comparing it to another international journal from the field and of similar orientation, Neoplasma, to illustrate ifdifferences and/or similarities between the two are in favour of or detriment to Radiology and Oncology. Results and conclusion. Results show thatRadiology and Oncology has been progressing in the right direction, but that extra efforts should be made by the editors and the editorial board to attract more articles per issue and to gradually increase the share of experimental articles to boost its impact in the field. Also, to improve its visibility, editors, reviewers and also authors that publish in Radiology and Oncology could consider citing the articles published in this journal, in the articles published elsewhere, when appropriate.
Keywords: Bibliometrics; Bibliometrija; Medical Oncology; Medicinska onkologija; Periodicals; Periodika; Radiologija; Radiology